2012
DOI: 10.2478/s11536-012-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression on multiple sclerosis patients

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Leonavicius et al [38] found sleep disturbances in 45.3 % of MS patients using the Medical Outcomes Study Sleep (MOSS) measure [39], and Tachibana et al [40] reported sleep problems in 53.6 % of MS patientsincluding discomfort in the legs, snoring, nocturia, and sleep apnea.…”
Section: Insomniamentioning
confidence: 99%
“…Leonavicius et al [38] found sleep disturbances in 45.3 % of MS patients using the Medical Outcomes Study Sleep (MOSS) measure [39], and Tachibana et al [40] reported sleep problems in 53.6 % of MS patientsincluding discomfort in the legs, snoring, nocturia, and sleep apnea.…”
Section: Insomniamentioning
confidence: 99%
“…Clinical studies have reported that sleep problems in MS are often under diagnosed [86], and may be related to daytime fatigue experienced by most of the patients [87]. There is also some evidence showing a positive correlation between the severity of the clinical picture and the presence of sleep problems [83], suggesting that the correction of sleep problems might help to improve the clinical conditions of MS patients. However, if this beneficial role of sleep is mediated by the mechanisms previously described on myelin and OPC proliferation remains unclear and needs further investigations.…”
Section: Oligodendrocytes and Opcs Pathology And Sleepmentioning
confidence: 99%
“…The current study demonstrated that depression was prevalent in 18.8 percent of study participants and that it was in line with previous studies. [30][31][32][33][34] Pain was presented in 84.2 percent of depressed patients and it was significantly higher compared with not depressed (54.9 percent) participants of the study (p < 0.01). The mean value of depression (HADS-D score) in patients' group with pain was significantly higher compared with pain free patients (respectively, 9.8 AE 5.2 vs. 6.1 AE 4.5, p < 0.01).…”
Section: Discussionmentioning
confidence: 75%